On the properties of velar/k/in kannada - H.S. Sridevi, S.R. Savithri (Journal of All India Institute of Speech and Hearing, 1970)
The stop consonants are produced by occluding the oral cavity by an articulator, behind which air is held for sometime and released. Acoustic analysis of stop consonants has showed five distinct segments namely occlusion, burst, frication, aspiration, and voiced format transitions.